Gene silencing pathways found in the green alga Volvox carteri reveal insights into evolution and origins of small RNA systems in plants. (December 2016) - Dueck, Anne; Evers, Maurits; Henz, Stefan; Unger, Katharina; Eichner, Norbert; Merkl, Rainer; Berezikov, Eugene; Engelmann, Julia; Weigel, Detlef; Wenzl, Stephan; Meister, Gunter
Abstract Background Volvox carteri (V. carteri) is a multicellular green alga used as model system for the evolution of multicellularity. So far, the contribution of small RNA pathways to these phenomena is not understood. Thus, we have sequencedV. carteri Argonaute 3 (VcAGO3)-associated small RNAs from different developmental stages. Results Using this functional approach, we define theVolvox microRNA (miRNA) repertoire and show that miRNAs are not conserved in the closely related unicellular algaChlamydomonas reinhardtii . Furthermore, we find that miRNAs are differentially expressed during different life stages ofV. carteri . In addition to miRNAs, transposon-associated small RNAs or phased siRNA loci, which are common in higher land plants, are highly abundant inVolvox as well. Transposons not only give rise to miRNAs and other small RNAs, they are also targets of small RNAs. Conclusion Our analyses reveal a surprisingly complex small RNA network inVolvox as elaborate as in higher land plants. At least the identified VcAGO3-associated miRNAs are not conserved inC. reinhardtii suggesting fast evolution of small RNA systems. Thus, distinct small RNAs may contribute to multicellularity and also division of labor in reproductive and somatic cells.